Central and peripheral psychophysiological responses to trauma-related cues in subclinical posttraumatic stress disorder: a pilot study - Wessa, Michèle; Karl, Anke; Flor, Herta (Experimental brain research, 2005)
This study examined verbal-subjective, peripheral and central physiological responses of motor vehicle accident (MVA) survivors with subclinical posttraumatic stress disorder (PTSD), without PTSD symptoms as well as healthy controls. Seven persons of each group were exposed to positive, neutral, accident-related and negative, non-accident-related slides. The verbal-subjective ratings of the slides did not differ between the groups. In contrast to the verbal ratings of the trauma-related materials, the behavioral and physiological responses showed a remarkable dissociation from these reports. The startle responses were enhanced to accident-related slides only in the PTSD group and MVA survivors with PTSD had a significantly lower response to the neutral slides than MVA survivors without PTSD. P200 was lower to positive, neutral and negative slides in the PTSD group compared to both other groups. The late positive complex showed no group-related effects. The data suggest that traumatized persons with PTSD show exaggerated emotional responses to trauma-related stimuli and reduced cognitive responses to several types of stimuli that may interfere with the extinction of the emotional trauma memory.
Gesehen am 04.11.2020